If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2x + 1) = 21 Reorder the terms: -3(1 + 2x) = 21 (1 * -3 + 2x * -3) = 21 (-3 + -6x) = 21 Solving -3 + -6x = 21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -6x = 21 + 3 Combine like terms: -3 + 3 = 0 0 + -6x = 21 + 3 -6x = 21 + 3 Combine like terms: 21 + 3 = 24 -6x = 24 Divide each side by '-6'. x = -4 Simplifying x = -4
| 5(4x-3)=11 | | 4y^3+12y^2+5y=0 | | 23=49-7x | | f(x)=x^3-2x^2+2x-6 | | 20-9w=4(15-1w) | | 11+9lnx=6 | | y+11=19 | | 9p+-5=1 | | 5x=81.2 | | 2x^2=-5x-10 | | z^(-3)/z^(-7) | | 87=2x-3(5x-3) | | -4(-2+2x)=-32 | | (9m-15)6=18 | | x^2-2x-15/6x^2-54 | | 5x^2+7x=4 | | -4(-4-6x)=88 | | 3x-8=58-2x | | 3(4x-1)-7x=16 | | 5x+26+14x=82 | | 2x^2+8=32 | | 3^(-4)/3 | | 32-3x=6x+21 | | x/7 | | 5x-8=2x+29 | | 3+5x+5x=83 | | 7x+2=4-(4x-7) | | 222-4x=179-44x | | 4x+7=x-5 | | -39-6x=-8x+11 | | 10/21=2a/a+b | | 10x-114=5x-14 |